Demographics and Culture: Strategic Drivers of Marketing Planning - Sri Lestari, Putri; Jubaedah, Dedah (Journal of Economicate Studies, 2022)
This study examines how demographics and culture shape strategic marketing planning, emphasizing the need for integrated approaches in a globalized world. It investigates how variables such as age, gender, income, and religion intersect with cultural values to influence consumer behavior and marketing effectiveness. Employing qualitative document analysis, the research synthesizes theoretical frameworks like STP and Hofstede's cultural dimensions to develop a composite model for market responsiveness. Findings reveal that while demographics define who the consumers are, culture determines how and why they engage with brands. The study offers both theoretical refinement and practical strategies, such as cultural persona mapping and localized messaging. It fills a notable gap in marketing literature by addressing the synergy between cultural and demographic insights, especially in emerging markets. Implications include more inclusive, adaptive, and data-driven marketing plans that resonate with diverse audiences.